2018
DOI: 10.30845/ijhss.v8n6a12
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Tourism-Horticulture Linkage among Smallholder Farmers in Zanzibar

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Horticultural tourism is "a niche market in green tourism and describes the benefits and potential of the green assets, such as public parks and recreation facilities, historic and heritage gardens, national and international horticultural events, rural farm visits, community gardens and farmers markets" [19] (p. 55). Previous work has suggested that the local origin of fruits and vegetables supplied by farmers are of crucial importance in the development of the relationship between horticulture and tourism [22]. In this sense, green spaces in urban environments are key in urban policy [42].…”
Section: The Integration Of Horticulture In Tourism Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Horticultural tourism is "a niche market in green tourism and describes the benefits and potential of the green assets, such as public parks and recreation facilities, historic and heritage gardens, national and international horticultural events, rural farm visits, community gardens and farmers markets" [19] (p. 55). Previous work has suggested that the local origin of fruits and vegetables supplied by farmers are of crucial importance in the development of the relationship between horticulture and tourism [22]. In this sense, green spaces in urban environments are key in urban policy [42].…”
Section: The Integration Of Horticulture In Tourism Experiencesmentioning
confidence: 99%
“…As part of urban sustainable development [18], horticulture conveys a sense of community identity [19] and urban gardens emerge as an avenue to "exemplify their locale to the world" [20] (p. 371). While previous research reveals that horticulture may have an important role in tourism and acknowledges the impact of tourism on community development through horticulture [21], the linkages between horticulture and tourism are still underexplored [22]. This paper aims to fill this research gap and its scientific value is based on the relevance of urban gardens as a source of sustainable development that increases the awareness of travelers to urban destinations.…”
Section: Introductionmentioning
confidence: 99%